Cutaneous inflammatory myofibroblastic tumours can be anaplastic lymphoma kinase‐positive: report of the first four cases. Issue 2 (7th August 2015) - Leguellec, Sophie; Tournier, Emilie; Karanian, Marie; Brousset, Pierre; Mazereeuw, Juliette; Coindre, Jean‐Michel; Lamant, Laurence
Abstract : Aims: Inflammatory myofibroblastic tumours (IMTs) usually have a soft tissue and visceral localization, but have been rarely reported in skin. The aim of this study was to characterize the histological and immunohistochemical features of a series of cutaneous IMTs. Methods and results: We retrieved from our archives over 10 years four cutaneous IMTs; one was diagnosed in a child, and three in young adults. Tumours were centred on the dermis, and also involved the subcutis in two cases. Two of them corresponded to the 'myxoid–vascular' pattern of IMT, whereas the others were characterized by compact fascicles of spindle‐shaped cells. They stained positively for smooth muscle actin. All samples stained positively for anaplastic lymphoma kinase (ALK). ALK expression was limited to the cytoplasm of myofibroblasts and, in the three investigated cases, correlated with ALK rearrangement as shown by fluorescence in‐situ hybridization analysis. Conclusions: This is the first report of ALK‐positive IMTs with a cutaneous localization. Because of their morphological heterogeneity and low incidence in skin, the diagnosis of cutaneous IMTs is often challenging. A cutaneous spindled cell tumour associated with an inflammatory infiltrate should prompt pathologists to perform ALK staining, which, if positive, might be decisive for diagnosis.